Students' Mathematical Problem Solving Ability of Class-VIII Through the Geogebra-Assisted POGIL Learning Model - Putri, Nabila Alifa Shandhita; Faradiba, Surya Sari; Khairunnisa, Gusti Firda (International Journal on Emerging Mathematics Education, 2024)
This study aims to determine differences in mathematical problem-solving abilities between the experimental class through the Geogebra-assisted POGIL (Process Oriented Guided Inquiry Learning) learning model and the control class through conventional learning and to determine mathematical problem-solving abilities after being treated with the POGIL (Process Oriented Guided Inquiry) by Geogebra-assisted. This study used a mixed method with a sequential-explanatory type. The study recruited class VIII of  SMPN 2 Prigen. The research sample was class VIII-A (the control class) and class VIII-C (the experimental class). The results showed that (1) there were differences in the mathematical problem-solving abilities of the experimental class through the Geogebra-assisted POGIL (Process Oriented Guided Inquiry Learning) learning model and the control class through conventional learning. (2) the mathematical problem-solving abilities of class VIII students of SMPN 2 Prigen using the Geogebra-assisted POGIL (Process Oriented Guided Inquiry Learning) learning model are better than using conventional learning models